Airlanggins A-B, two new isoprenylated benzofuran-3-ones from the stem bark of Calophyllum soulattri - Tanjung, Mulyadi (Taylor & Francis, 2017)
ABSTRACT Two new isoprenylated benzofuran 3-ones, airlanggin A (1) and B (2) along with two known xanthones, ananixanthone (3) and trapezifolixanthone (4) were isolated from the stem bark of Calophyllum soulattri. Structures of all the compounds were elucidated using extensive spectroscopic methods, including UV, IR, HRESIMS, 1D and 2D NMR. Compounds 1–4 were evaluated for their cytotoxicity against P-388 cells, showing that compound 3 was the most active with IC50 0.68 μg/mL and compound 1 showed moderate activity with IC50 5.80 μg/mL.